Scientific-practical Conference. Innovations in Nursing Science: 2025. Conference Abstracts - Urbanavičė, Rita (Slauga. Mokslas ir praktika, 2025)
The scientific and practical conference "Nursing Science Innovations: 2025" brought together Lithuanian and foreign general nurses, advanced practice nurses, students of all levels of nursing study programmes, nursing researchers, and scientists to present the latest achievements in nursing science, share research results, and discuss current topics of nursing science and practice. The abstracts of the conference presentations published in this journal supplement reflect three main thematic areas: nursing research, presenting research in English by Lithuanian and foreign researchers; clinical nursing research, focusing on the evaluation of practical interventions, improving the quality of patient care, and evidence-based practice; and nursing education, focusing on the use of innovative teaching methods and the development of nurses’ professional competencies. We thank the conference organisers for their ideas, efforts, and work and the conference scientific committee for their peer review and evaluation of the abstracts. We hope this publication will stimulate scientific discussion, contribute to the dissemination of nursing science, and inspire conference participants to further research relevant to academia and nursing practice.